0590 Reliability of Simple Sleep Evaluation Device at Split-Night Polysomnography. (27th May 2020) - Adachi, T; Koba, S; Hanyu, A; Kato, M; Morita, M; Kawamoto, T; Ida, H; Watanabe, Y; Shinke, T
Abstract: Introduction: Watch-PAT is a sleep evaluation device that measures the peripheral blood volume continuously with a probe attached to a fingertip and does not use an electroencephalogram or a nasal cannula. There has been no report on the usefulness of watch-PAT to determine the apnea diagnosis and continuous positive airway pressure (CPAP) use effects in split-night sleep study. Methods: The consent of the study was obtained. Watch-PAT was simultaneously worn on a patient admitted for split-night polysomnography. The apnea-hypopnea index (AHI) obtained from PSG and the pAHI gained from the watch-PAT were measured when not using CPAP and when using CPAP respectively. And also we examined whether the reduction rates of AHI and pAHI could be correlated. Results: 38 subjects (32 men, age 55 ± 13 years old). BMI 28.3 ± 5.7 kg / m 2 . When CPAP was not used, AHI was 57.2 ± 23.3 / h and pAHI was 50.8 ± 20.3 / h (r = 0.93, p < 0.0001), when CPAP was used, AHI was 5.2 ± 4.5 /h and pAHI was 6.2 ± 4.5 h (r = 0.82, p < 0.0001), AHI reduction rate was 90.4 ± 8.0% and pAHI reduction rate was 85.4 ± 14.6% (r = 0.76, p < 0.0001). Conclusion: It was suggested that Watch-PAT had a good correlation with AHI at split night-sleep study. Support: None